Practices of Translanguaging in English Classroom in Indonesian EFL context: A CaseStudy - Azzahra Qur'ani Putri; Siti Asmiyah; Irwan Puji Prasetyo (English Education:Journal of English Teaching and Research, 2026)
Translanguaging has been widely studied in the multilingual context of English language learning, but in-depth research on specific cases has not been conducted yet. This study aims to identify translanguaging practices in Indonesian classroom. Through a case study, this qualitative research collected data from classroom observations and analysis of teacher-studentinteractions recordings. Based on the classroom observation data, this study highlights various translanguaging practices carried out by teachers and students using Indonesian, English, and Javanese in English classes of 36 students. Translanguaging practices were implemented during learning sessions, including openings, main activities, and closings. The data reflect interlanguage interactions in EFL contexts in a multicultural and multilingual countrylike Indonesia. The findings indicate that translanguaging is an effective and natural practice in Indonesian EFL classrooms and has the potential to support a more inclusive and communicative language learning process. The data from the classroom observations highlight various translanguaging practices by both teachers and students using Indonesian, English, and Javanese in combination. The data reflect interlanguage interactions in EFL contexts in a multicultural and multilingual countrylike Indonesia.